Emergency medical services at the crossroads (Future of emergency care., 2007)
Emergency Medical Services (EMS) is a critical component of our nation's emergency and trauma care system, providing response and medical transport to millions of sick and injured Americans each year. At its best, EMS is a crucial link to survival in the chain of care, but within the last several years, complex problems facing the emergency care system have emerged. Press coverage has highlighted instances of slow EMS response times, ambulance diversions, trauma center closures, and ground and air medical crashes. This heightened public awareness of problems that have been building over time has underscored the need for a review of the U.S. emergency care system. Emergency Medical Services provides the first comprehensive study on this topic. This new book examines the operational structure of EMS by presenting an in-depth analysis of the current organization, delivery, and financing of these types of services and systems. By addressing its strengths, limitations, and future challenges this book draws upon a range of concerns: (1) The evolving role of EMS as an integral component of the overall health care system; (2) EMS system planning, preparedness, and coordination at the federal, state, and local levels; (3) EMS funding and infrastructure investments; (4) EMS workforce trends and professional education; (5) EMS research priorities and funding.